Exploring Parental Control and its Impact on Secondary Level Students’ Attitude Towards Studies - Mushtaq Ahmad, Farah Shafiq, Muhammad Nadeem Anwar (JCTE, 2023)
In the present study, we examined the relationship between parental control and secondary level students’ attitude towards studies. The population of the study was the male and female Secondary level students and their parents of all the boys’ and girls’ government secondary schools of Tehsil Sargodha. A sample of 150 students of the10th class and their parents were selected on an availability basis from the randomly selected 30 secondary schools including 10 Boys and 20 Girls schools. Two self-developed research instruments including one for parents’ control and the other for students’ attitude were used. To analyse the data, statistical calculations including frequency, percentage, mean score, standard deviation, t-test, one-way ANOVA and correlation were used. The findings showed that the parents with more public dealing professions tend towards the strict and highly strict level of parental control and there exist a positive and moderate relationship between parental control and students’ attitude towards studies. The study recommends that parent teacher regular meetings may be organized for parents ‘awareness to adopt better control strategy.